Kemampuan Pemecahan Masalah Matematika Ditinjau dari Kemampuan Awal Matematika dan Perbedaan Gender - Erni Apriani; Djadir; Asdar (Issues in Mathematics Education (IMED), 2017)
This research is a qualitative descriptive research that aims to describe the ability of problem solving mathematically viewed from the early ability of mathematics and gender differences. The subjects of this study were six students. The six students were selected based on the Mathematics Ability test scores divided into high, medium, and low categories with two men each and one woman representing each level of math skills on SPLDV material by taking the highest grades from each capability category. The six subjects were given the Mathematical Problem Solving Ability Test I and the Mathematics Problem Solving Ability Test II at different times. Data analysis techniques using qualitative analysis. The results of this study indicate that: (1) Indicators mention things that are known and questioned by all subjects, (2) Indicators to make problem-solving plans from things known for problem solving are shared by all subjects, (3) Indicators carry out problem solving through a plan that has been made owned by all subjects, (4) Indicators of re-examination of existing answers owned by all subjects.